Seroma em lipoabdominoplastia e abdominoplastia convencional: estudo comparativo - Di Martino, Marcello [UNIFESP] (2009)
Introduction: Abdominoplasty is one of the most frequently performed cosmetic procedures and its combination with liposuction has become more common. Seroma is one of the most common complications in abdominoplasty.Objective: To compare the rate of seroma formation in patients who underwent either abdominoplasty without the use of quilting sutures, or lipoabdominoplasty. Methods: The sample consisted of 41 female patients, who were divided into two groups and underwent one of the following procedures: group A (n=21), abdominoplasty without quilting sutures and group B (n=20), lipoabdominoplasty. In order to investigate seroma formation, abdominal ultrasound was performed in 5 regions of the abdominal wall [epigastrium (EPI), umbilical (UMB), hypogastrium (HYPO), right iliac fossa (RIF) and left iliac fossa (LIF)], at two postoperative periods: (P1), between postoperative days 11 and 14, and (P2), between postoperative days 18 and 21. Results: The rate of seroma formation P1 was 38,1% in group A and 10,0% in group B. In P2 the rate of seroma formation was 33,3% in group A and 0,0% in group B. It was observed that, in group A at P1, the regions RIF and LIF developed larger fluid collections. In group B, there were significantly larger fluid collections in the HYPO region at P1, and in the UMB and HYPO regions at P2. Conclusion: Lipoabdominoplasty is a effective techniques for the prevention of seromas compared with conventional abdominoplasty.